Optimization of shopping center construction under organizational and financial constraints - Meneiliuk, Ivan; Nikiforov, Oleksiy (Academic journal Industrial Machine Building Civil Engineering, 2019)
The article presents the results of optimizing the construction duration of the object and the average monthly financing intensity of the shopping center construction under organizational and financial constraints, namely: the work processes alignment – 68-76%; the maximum monthly financing intensity – 40 million UAN; number of work brigades – 1-2; the maximum construction duration – 360 days. There were developed the method for optimizing and the results of numerical modeling of organizational and financial decisions were obtained. The most efficient models of construction were identified by graphical way under limited conditions of their implementation.